THERMODYNAMIC ESTIMATION OF MGO DISSOLUTION IN SLAGS OF STEELMAKING - V. F. Sobolev; S. V. Terletskij; A. A. Chichko (Литьë и металлургия)
The results of thermo-dynamic methods of calculation of MgO dissolution in steel-smelting slags of high basic capacity, forthcoming by composition to the applied ones in practice of the metallurgical production BMZ, are presented. The equation for calculation of extreme dissolution of MgO in slag on the basis of thermodynamic characteristics of compound is received.